Calculating the risk of a pancreatic fistula after a pancreaticoduodenectomy: a systematic review. Issue 11 (November 2015) - Vallance, Abigail E.; Young, Alastair L.; Macutkiewicz, Christian; Roberts, Keith J.; Smith, Andrew M.
Abstract Background A post‐operative pancreatic fistula (POPF) is a major cause of morbidity and mortality after a pancreaticoduodenectomy (PD). This systematic review aimed to identify all scoring systems to predict POPF after a PD, consider their clinical applicability and assess the study quality. Method An electronic search was performed of Medline (1946–2014) and EMBASE (1996–2014) databases. Results were screened according to Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines, and quality assessed according to the QUIPS (quality in prognostic studies) tool. Results Six eligible scoring systems were identified. Five studies used the International Study Group on Pancreatic Fistula (ISGPF) definition. The proposed scores feature between two and five variables and of the 16 total variables, the majority (12) featured in only one score. Three scores could be fully completed pre‐operatively whereas 1 score included intra‐operative and two studies post‐operative variables. Four scores were internally validated and of these, two scores have been subject to subsequent multicentre review. The median QUIPS score was 38 out of 50 (range 16–50). Conclusion These scores show potential in calculating the individualized patient risk of POPF. There is, however, much variation in current scoring systems and further validation in large multicentre cohorts is now needed.